2020
DOI: 10.1001/jama.2020.0592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Machine Learning–Derived Early Warning System for Intraoperative Hypotension vs Standard Care on Depth and Duration of Intraoperative Hypotension During Elective Noncardiac Surgery

Abstract: IMPORTANCEIntraoperative hypotension is associated with increased morbidity and mortality. A machine learning-derived early warning system to predict hypotension shortly before it occurs has been developed and validated.OBJECTIVE To test whether the clinical application of the early warning system in combination with a hemodynamic diagnostic guidance and treatment protocol reduces intraoperative hypotension.DESIGN, SETTING, AND PARTICIPANTS Preliminary unblinded randomized clinical trial performed in a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
328
6
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 357 publications
(356 citation statements)
references
References 25 publications
12
328
6
10
Order By: Relevance
“…Explanation: Describe the intended use of the AI intervention in the trial report title and/or abstract. This should describe the purpose of the AI intervention and the disease context 2644. Some AI interventions may have multiple intended uses or the intended use may evolve over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanation: Describe the intended use of the AI intervention in the trial report title and/or abstract. This should describe the purpose of the AI intervention and the disease context 2644. Some AI interventions may have multiple intended uses or the intended use may evolve over time.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recognised that most recent AI studies are inadequately reported and existing reporting guidelines do not fully cover potential sources of bias specific to AI systems 25. The welcome emergence of randomised controlled trials (RCTs) seeking to evaluate newer interventions based on, or including, an AI component (hereafter “AI interventions”)23262728293031 has similarly been met with concerns about the design and reporting 25323334. This has highlighted the need to provide reporting guidance that is “fit-for-purpose” in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…Goal-directed hemodynamic therapy based on HPI reduced the incidence, severity, and duration of intraoperative hypotension compared with the control groups. In a small single-center preliminary randomized trial including 68 adult patients scheduled for elective noncardiac surgery under general anesthesia, Wijnberge et al 88 showed that the use of the HPI in combination with a hemodynamic management protocol reduced the time-weighted average below a MAP of 65 mm Hg (i.e., the area under a MAP of 65 mm Hg divided by the duration of surgery) compared with standard care. In the future, the optimal hypotension threshold per patient might be determined using predictive analytics (machine learning), further personalizing hemodynamic treatment.…”
Section: Automation and The Futurementioning
confidence: 99%
“…8 We further established an elemental regression equation between parturient vertebral column length, abdominal girth, and 0.5% hyperbaric intrathecal bupivacaine volume for T5 block level [9]. 9 However, the sample size in these studies was relatively small and the accuracy of the regression equation needed further verification [8,9] In recent years, there has been an advance in machine-learning algorithms in a number of fields including anesthesiology, which allowed large amounts of data for development of robust predictive analytics [10][11][12][13]. These were used to predict, inter alia, postinduction hypotension [13].…”
Section: Introductionmentioning
confidence: 99%
“…These were used to predict, inter alia, postinduction hypotension [13]. intraoperative hypotension [11], and length of hospital stay [14]. In our hospital, more than 1000 parturient women undergo cesarean section under spinal anesthesia annually.…”
Section: Introductionmentioning
confidence: 99%